The calculations of uranium and lanthanum oxides trajectories at magnetoplasma separation stage - Yuferov, V.B.; Tkachova, T.I.; Katrechko, V.V.; Svichkar, A.S.; Ilichova, V.O.; Shariy, S.V. (Вопросы атомной науки и техники, 2017)
Trajectories of charged particles (UO₂ and La₂O₃) at magnetoplasma separation stage – in system of crossed electric and magnetic fields – are calculated. The possibilities of UO₂ separation from La₂O₃ by changes in magnetic and electric fields components are investigated. Adding of certain changes in magnetic field distribution does not lead to the solution of problem, while the addition of variable component to constant radial electric field allows to separate the nuclear fuel from lanthanides complex compounds at magnetoplasma separation stage. Рассчитаны траектории движения заряженных частиц (UO₂ и La₂O₃) на стадии магнитоплазменного разделения – в системе скрещенных электрического и магнитного полей. Исследованы возможности отделения UO₂ от La₂O₃ путём внесения изменений в компоненты магнитного и электрического поля. Внесение определённых изменений в распределение магнитного поля не даёт желаемых результатов, а добавление переменной компоненты к постоянному радиальному электрическому полю позволяет отделить ядерное топливо от сложных соединений лантаноидов на стадии магнитоплазменного разделения. Розраховано траєкторії руху заряджених частинок (UO₂ і La₂O₃) на стадії магнітоплазмового розділення − в системі схрещених електричного і магнітного полів. Досліджено можливості відділення UO₂ від La₂O₃ шляхом внесення змін до компонент магнітного і електричного полів. Внесення певних змін у розподіл магнітного поля не дає бажаних результатів, а додавання змінної компоненти до постійного радіального електричного поля дозволяє відокремити ядерне паливо від складних з'єднань лантаноїдів на стадії магнітоплазмового розділення.